Flipping the Training in Health Professions Education - Tabassum Naveed , Naveed Mazhar Bhatti , Romana Malik , Tabassum Naveed , Naveed Mazhar Bhatti , Romana Malik (Journal of Rawalpindi Medical College, 2017)
Background: To study the flipping or inverted method of teaching in health professionals involved in medical education Method: A cross sectional study was conducted to collect data about perception of faculty regarding flipped method as a faculty training method. Convenient method of sampling was done to collect data from 31 participants. Specific objective for this purpose was to determine if there was a significant difference from the normal in perception of faculty trained by flipping the classroom? We hypothesized that there will be a significant difference in perception of faculty trained in a flipped classroom as compared to normal. The average score on the questionnaire was taken as a reference for normal. Results: The results of the study were statistically significant at 95% confidence interval, t (30) = 7.43, p = 0.000<0.05. Conclusion: Faculty had a positive perception about flipped method of training. This method is useful and feasible for faculty training